Adsorption of Carbon Dioxide by Metal Organic Framework for Indoor Air Quality Enhancement. Issue 1 (November 2021) - Chong, K.C.; Lee, S.S.; Lai, S.O.; Thiam, H.S.; Ho, P.S.; Lau, W.J.
Abstract: Air pollution has become a severe environmental issue among millions of people around the globe. However, the risk of exposure to indoor air pollution is much higher than outdoor air pollution. The most effective way to improve indoor air quality (IAQ) by reducing the indoor CO2 content is by capturing and storing. There are several types of adsorbents used to capture CO2, namely physical adsorbents and chemical adsorbents. Metal-Organic Framework (MOF) is one of the recent interests arising physical adsorbents which possesses high adsorption capability. In this study, MOFs fabricated with different metals and organic ligands were used to evaluate their performance in CO2 adsorption under an enclosed office space. Magnesium, chromium, and copper metals were used as the main element in the MOF fabrication coupled with trimesic acid as an organic ligand. The MOFs' morphologies generally illustrated that magnesium MOF exhibited a dispersed nanorod flask crystal, chromium MOF showed agglomeration crystal, whereas fine crystal rod was observed in copper MOF. The elemental analysis from EDX and XRD confirmed that the metals were successfully embedded with the organic ligand, which is similar to the literature studies. The CO2 gas adsorption study suggested that magnesium MOF fabricated with trimesic acid possess superior CO2 adsorption capability as the recorded CO2 concentration reduced from 960 ± 73 ppm to 895 ± 57 under 2 hours continuous sampling time. The CO2 adsorption study reveals that the magnesium MOF with trimesic acid ligand yields a promising result on indoor CO2 concentration reduction. This result suggested that the MOF possesses a great potential to be applied in the indoor air quality enhancement with the integration to the existing air purification and/or filtration system.